129 Does pulse oxygen saturation (SpO2) in room air correlate with length of stay in infants with acute bronchiolitis?. (17th August 2022) - Mowat, Victoria; Cunningham, Steve
Abstract : Aims: Clinical outcome measures in bronchiolitis are frequently subjective and highly variable. We wished to evaluate whether the regular measurement of SpO2 in room air offers a good objective measure of recovery in infants with bronchiolitis. Methods: Repeated values of SpO2 on room air during admission of 54 infants admitted with bronchiolitis were recorded. Patients with more than five values for SpO2 in room air (n=53) were included. We plotted values against time to discharge for each child and calculated a correlation coefficient. We also analysed a sub-group (n=33) of infants where initial SpO2 was <94%. Wilcoxon ranked sum was used to compare correlation co-efficients with time to discharge in each group. Results: In the group as a whole there was a significant association between individual correlation co-efficients and time to discharge (p<0.0001). For 81% of patients (43/53) the correlation co-efficient was positive (see figure 1). In those with an initial SpO2 <94%, a positive correlation co-efficient was seen in 100% (n=31) and this too was a significant association (p<0.0001). The mean (standard deviation) correlation coefficients were 0.261 (0.455) for the whole group and 0.593 (0.232) for those with initial SpO2 <94%. Conclusion: A positive correlation for trend to improvement in SpO2 and length of stay, is observed especially in those whose initial SpO2 is <94% in room air. Although there is a reasonable positive correlation coefficient and the statistically significant association, the standard deviation remains high. Therefore the inter person variability appears too high to consider this a potentially reliable trial outcome for interventions in acute bronchiolitis.